Enamel interproximal reduction during treatment with clear aligners: digital planning versus OrthoCAD analysis - Giuseppina Laganà; Arianna Malara; Roberta Lione; Carlotta Danesi; Simonetta Meuli; Paola Cozza (BMC, 2021)
Abstract Background The aim of the study was to compare the amount of interproximal enamel reduction (IPR) provided on ClinCheck software with the amount of IPR carried out by the orthodontist during treatment with clear aligners. Methods 30 subjects (14 males, 16 females; mean age of 24.53 ± 13.41 years) randomly recruited from the Invisalign account of the Department of Orthodontics at the University of Rome "Tor Vergata" from November 2018 to October 2019, were collected according to the following inclusion criteria: mild to moderate dento-alveolar discrepancy (1.5-6.5 mm); Class I canine and molar relationship; full permanent dentition (excluding third molars); both arches treated only using Comprehensive Package by Invisalign system; treatment plan including IPR. Pre- (T0) and post-treatment (T1) digital models (.stl files), created from an iTero scan, were collected from all selected patients. The OrthoCAD digital software was used to measure tooth mesiodistal width in upper and lower arches before (T0) and at the end of treatment (T1) before any refinement. The widest mesio-distal diameter was measured for each tooth excluding molars by "Diagnostic" OrthoCAD tool. The total amount of IPR performed during treatment was obtained comparing the sum of mesio-distal widths of all measured teeth at T0 and T1. Significant T1-T0 differences were tested with dependent sample t-test (P < 0.05). Results In the upper arch, IPR was digitally planned on average for 0.62 mm while in the lower arch was on average for 1.92 mm. As for the amount of enamel actually removed after IPR performing, it was on average 0.62 mm in the maxillary arch. In the mandibular arch, the mean of IPR carried out was 1.93 mm. The difference between planned IPR and performed IPR is described: this difference was on average 0.00 mm in the upper arch and 0.01 in the lower arch. Conclusions The amount of enamel removed in vivo corresponded with the amount of IPR planned by the Orthodontist using ClinCheck software.